Non-phasematched sum frequency generation from tightly focused high gain parametric down conversion - Kopylov, D. A.; Spasibko, K. Yu; Leuchs, Gerd; Murzina, T. V.; Chekhova, Maria V. (Proceedings - International Conference Laser Optics 2018, ICLO 2018, 2018)
We study the sum frequency generation from high gain parametric down conversion with broadband spectrum in the absence of the phase matching. In the case of strong focusing, a set of interference spectral peaks in the spectrum of the second harmonic appear without the phase matching. Experimental data supported by theoretical modeling reveal the influence of correlation effects on non-phase matched sum frequency generation.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Gaussian beams; Optical harmonic generation; Parametric down conversion